Managing Information / Certificate in Management: Book One - The University Of York (Financial Times Management)
Introduction, What is Information and Why is it Important?, Defining your Information Needs, Information in your Organisation, Evaluating Information, Sources of Information, Obtaining Information, Storing Information, Developing Storage Systems.
Introduction, What is Information and Why is it Important?, Defining your Information Needs, Information in your Organisation, Evaluating Information, Sources of Information, Obtaining Information, Storing Information, Developing Storage Systems.